Sensorineural hearing loss in children with sickle cell disease. (March 2019) - Farrell, Annie N.; Landry, April M.; Yee, Marianne E.; Leu, Roberta M.; Goudy, Steven L.
Abstract: Introduction: Sensorineural hearing loss (SNHL) has been reported to occur at increased frequency in the pediatric sickle cell disease (SCD) population, likely secondary to ototoxic medication regimens and repeat sickling events that lead to end organ damage. Risk and protective factors of SNHL in this population are not fully characterized. The objective of this study was to describe audiology results in children with SCD and the prevalence and sequelae of SNHL. Methods: A comprehensive clinical database of 2600 pediatric SCD patients treated at 1 institution from 2010-16 was retrospectively reviewed to identify all patients who were referred for audiologic testing. Audiologic test results, patient characteristics, and SCD treatments were reviewed. Results: 181 SCD children (97 male, 153 HbSS) underwent audiologic testing, with 276 total audiology encounters, ranging 1–9 per patient. Mean age at first audiogram was 8.9 ± 5.2 years. 29.8% had prior cerebrovascular infarct and an additional 25.4% had prior abnormal transcranial Doppler screens documented at time of first audiogram. Overall, 13.3% had documented hearing loss, with 6.6% SNHL. Mean pure tone average (PTA) among patients with SNHL ranged from mild to profound hearing loss (Right: 43.3 ± 28.9, Left: 40.8 ± 29.7), sloping to more severe hearing loss at higher frequencies. Conclusions: Hearing loss was identified in a significant subset of children with SCD and the hearing loss ranged from normal to profound. Though the overall prevalence of SNHL in SCD patients was low, baseline audiology screening should be considered.